2010 IEEE International Conference on Communications 2010
DOI: 10.1109/icc.2010.5502331
|View full text |Cite
|
Sign up to set email alerts
|

On the Best Way to Cut a Body Area Network's Wires

Abstract: New technologies can help to develop preventive healthcare, thereby leading to significant life quality improvements. Medical Body Area Networks are expected to become a key element in tomorrow's medical IT infrastructure by enabling the long term collection and analysis of health parameters. For this vision to become a reality, several challenges must be addressed. This work focuses on the technological aspects of ultra low power consumption, low latency and packet error rate. We consider and evaluate state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A comparative study is reported in [45] which compares IR-UWB, FM-UWB, and a commercially available narrow band radio in terms of power consumption, reliability, and latency. The UWB specifications were partially taken from the WPAN standard and also from the WBAN draft standard.…”
Section: Compact Comparison Of the Standardsmentioning
confidence: 99%
“…A comparative study is reported in [45] which compares IR-UWB, FM-UWB, and a commercially available narrow band radio in terms of power consumption, reliability, and latency. The UWB specifications were partially taken from the WPAN standard and also from the WBAN draft standard.…”
Section: Compact Comparison Of the Standardsmentioning
confidence: 99%
“…The proposed dual-radio approach for the medicine diffusion device is illustrated in Figure 2. By using this approach, there is no need to implement UWB receiver to the sensor node which is more power consuming than UWB transmitter [20]. The hub node includes IEEE Std.…”
Section: System Modelmentioning
confidence: 99%